Involvement of p21racA, phosphoinositide 3-kinase, and vacuolar ATPase in phagocytosis of bacteria and erythrocytes by Entamoeba histolytica: suggestive evidence for coincidental evolution of amebic invasiveness. - Ghosh, S K (1997)
Trophozoites of Entamoeba histolytica, the protozoan parasite that causes amebic dysentery, phagocytose bacteria in the colonic lumen and erythrocytes (RBC) in host tissues. Because tissue invasion is an evolutionary dead end, it is likely that amebic pathogenicity is coincidentally selected, i.e., the same methods used to kill bacteria in the colonic lumen are used by parasites to damage host cells and cause disease. In support of this idea, the amebic lectin and pore-forming peptide are involved in binding and killing, respectively, bacteria and host epithelial cells. Here amebic phagocytosis of bacteria, RBC, and mucin-coated beads was disrupted by overexpression of E. histolytica p21(racA-V12), a ras-family protein involved in selection of sites of actin polymerization, which had been mutated to eliminate its GTPase activity. p21(racA-V12) transformants were also defective in capping and cytokinesis, while pinocytosis of fluorescent dextrans was not affected. Wortmannin, a fungal inhibitor of phosphoinositide 3-kinase, markedly inhibited phagocytosis of bacteria, RBC, and mucin-coated beads by wild-type amebae. In contrast to p21(racA-V12) overexpression, wortmannin abolished amebic pinocytosis of dextrans but had no inhibitory effects on capping. Inhibition of amebic vacuolar acidification by bafilomycin also decreased bacterial and RBC uptake. These results, which demonstrate similarities between mechanisms of phagocytosis of bacteria and RBC by amebae and macrophages, support the idea of coincidental selection of amebic genes encoding proteins that mediate destruction of host cells.